Density Based Clustering algorithm for Vehicular Ad-Hoc Networks. (25th September 2009) - Kuklinski, Slawomir; Wolny, Grzegorz
In this paper we present a new multilevel clustering algorithm for Vehicular Ad-Hoc Networks (VANET), which we call the Density Based Clustering (DBC). Our solution is focused on the formation of stable, long living clusters. Cluster formation is based on a complex clustering metric which takes into account the density of the connection graph, the link quality and the road traffic conditions. The tests performed in the simulation environment composed of VanetMobiSim and Java in Simulation Time (JiST)/SWANS have shown that DBC performs better than the popular approach (the Lowest Id algorithm) – the clusters stability has been significantly increased.